Five‐year outcomes after iodine‐125 seed brachytherapy for low‐risk prostate cancer at three cancer centres in the UK. (2nd December 2013) - Dickinson, Peter D.; Malik, Jahangeer; Mandall, Paula; Swindell, Ric; Bottomley, David; Hoskin, Peter; Logue, John P.; Wylie, James P.
Abstract : Objective: To report the outcomes of >1000 men with low‐risk prostate cancer treated with low‐dose‐rate (LDR) brachytherapy at three large UK cancer centres. Patients and Methods: A total of 1038 patients with low‐risk prostate cancer (prostate‐specific antigen [PSA] ≤10 ng/mL, Gleason score 6, ≤T2b disease) were treated with LDR iodine 125 (I‐125) brachytherapy between 2002 and 2007. Patients were treated at three UK centres. PSA and clinical follow‐up was performed at each centre. Biochemical recurrence‐free survival was reported for the cohort. Results: The median (range) PSA follow‐up for the whole group was 5 years (4 months to 9 years). A total of 79 patients had biochemical failure, defined by a rise in PSA level: 16 patients fulfilled the ASTRO definition of biochemical failure, 25 patients fulfilled the Phoenix definition and 38 patients fulfilled both definitions. The 5‐year biochemical relapse‐free survival (bRFS) rate was 94.1% by the ASTRO definition and 94.2% by the Phoenix definition. The absence of neoadjuvant hormone therapy was predictive of inferior biochemical control as defined by the Phoenix definition (P = 0.033). Conclusions: Our prospective multicentre series showed excellent bRFS with LDR I‐125 brachytherapy for patients with low‐risk prostate cancer. Further work is necessary to define the role of neoadjuvant androgen deprivation therapy in combination with brachytherapy.